Estudo de associação entre polimorfismos de base única com características de eficiência de conversão, consumo e desempenho em bovinos da raça Nelore - Olivieri, Bianca Ferreira [UNESP] (2015)
The need to turn the beef production more profitable and at the same time sustainable, the traits associated with feed efficiency are gaining importance. The residual feed intake (RFI), suggested as a parameter for feed efficiency and it has become a tool for the selection of more efficient animals. In recent years, a large number of genomic tools become available due to advancement of the technology of molecular markers, such as SNPs. Therefore, genomic regions associated with the SNP markers for residual feed intake (RFI), weight gain and other traits related to feed efficiency have a promising future, with selection of more efficient animals. This study aimed to associate genomic data from the use of highdensity chips to identify QTL regions linked to traits such as feed efficiency, weight gain, feed intake and CAR 896 Nelore cattle, from the Animal Science Institute, located in Sertãozinho. The model used for the prediction of breeding values of the traits was the ssGBLUP. This ssGBLUP model, besides using phenotypic and genotypic data, also use pedigree information. With the results of genomic association studies, it was performed the search for genes to identify SNPs that were associated with the feed efficiency indicators and seek genetic regions and genes that may, in fact, influence the expression of the traits. To determine the possible QTL regions, the segments that explain values greater than or equal to 1% of the additive genetic variance were selected. A total of 51 genomic regions for the studied traits were found. For identification and positioning of the SNPs in the bovine genome was conducted a survey on the database available in the NCBI and Ensembl. The classification of genes as biological function was performed by the website DAVID. The heritability estimate for feed efficiency was low (0.13), moderate for residual feed intake (0.18), and moderate to high magnitude for weight gain (0.43) and feed intake (0.47). A ...